Broad Virus Detection and Variant Discovery in Fecal Samples of Hematopoietic Transplant Recipients Using Targeted Sequence Capture Metagenomics - Jansen, Suze A.; Nijhuis, Wouter; Leavis, Helen L.; Riezebos-Brilman, Annelies; Lindemans, Caroline A.; Schuurman, Rob (Frontiers in Microbiology, 2020)
Pediatric allogeneic hematopoietic stem cell transplantation (HSCT) patients often suffer from gastro-intestinal (GI) disease caused by viruses, Graft-versus-Host Disease (GVHD) or a combination of the two. Currently, the GI eukaryotic virome of HSCT recipients remains relatively understudied, which complicates the understanding of its role in GVHD pathogenicity. As decisions regarding immunosuppressive therapy in the treatment of virus infection or GVHD, respectively, can be completely contradicting, it is crucial to better understand the prevalence and relevance of viruses in the GI tract in the HSCT setting. A real time PCR panel for a set of specific viruses widely used to diagnose the most common causes of GI viral gastroenteritis is possibly insufficient to grasp the full extent of viruses present. Therefore, we applied the targeted sequence capture method ViroCap to residual fecal samples of 11 pediatric allogeneic HSCT recipients with GI symptoms and a suspicion of GVHD, to enrich for nucleic acids of viruses that are known to infect vertebrate hosts. After enrichment, NGS was applied to broadly detect viral sequences. Using ViroCap, we were able to detect viruses such as norovirus and adenovirus (ADV), that had been previously detected using clinical diagnostic PCR on the same sample. In addition, multiple, some of which clinically relevant viruses were detected, including ADV, human rhinovirus (HRV) and BK polyomavirus (BKV). Interestingly, in samples in which specific PCR testing for regular viral GI pathogens did not result in a diagnosis, the ViroCap pipeline led to the detection of viral sequences of human herpesvirus (HHV)-7, BKV, HRV, KI polyomavirus and astrovirus. The latter was an only recently described variant and showed extensive sequence mismatches with the applied real time PCR primers and would therefore not have been detected if tested. Our results indicate that target enrichment of viral nucleic acids through ViroCap leads to sensitive and broad possibly clinically relevant virus detection, including the detection of newer variants in clinical HSCT recipient samples. As such, ViroCap could be a useful detection tool clinically, but also in studying the associations between viral presence and GVHD.